Cultural stewardship in urban spaces: Reviving Indigenous knowledge for the restoration of nature - Walker E; Jowett T; Whaanga H; Wehi PM (John Wiley & Sons Ltd on behalf of British Ecological Society, 2024)
Relationships to nature are important for the health and well-being of peoples globally and should be actively protected. Indigenous Māori people in Aotearoa New Zealand recognize this important relationship to nature through narratives of lineage and express this through concepts such as kaitiakitanga; a cultural place-based practice of stewardship that intertwines relationships of responsibility between people, nature and culture. However, many Māori now live outside of tribal areas in urban settings, putting relationships with nature into question. We asked how urban Māori people practice kaitiakitanga, and what factors might predict flourishing relationships with nature. We surveyed 214 urban Māori who shared their perceptions of kaitiakitanga, cultural practices and restoration activities. The data were analysed by identifying qualitative themes and using linear mixed effect models. Māori who were exposed to kaitiakitanga as children were more likely to attend marae and family restoration activities, and less likely to attend events led by local councils. Pressingly, young people in urban areas were more at risk of losing cultural knowledge and opportunities to practice cultural practices in urban areas. Age, distance from tribal area and early exposure all affected decision-making and expression of kaitiakitanga in urban areas. Knowledge associated with kaitiakitanga can create inclusive and effective urban restoration activities. We suggest that partnership between Māori groups including local marae, and local councils, may provide accessible, best practice urban restoration models that attract local Māori and act to support cultural knowledge, in turn encouraging diverse pathways to nature restoration to develop in urban areas. Likewise, such partnerships will ensure that Māori in cities are supported to express and maintain cultural knowledge and practice into the future. Read the free Plain Language Summary for this article on the Journal blog.
Keywords: Indigenous knowledge; Indigenous practice; Indigenous urban restoration; Indigenous urbanism; kaitiakitanga; urban restoration